What constitutes clinically significant binge eating? Association between binge features and clinical validators in college‐age women. Issue 3 (6th February 2013) - Vannucci, Anna; Theim, Kelly R.; Kass, Andrea E.; Trockel, Mickey; Genkin, Brooke; Rizk, Marianne; Weisman, Hannah; Bailey, Jakki O.; Sinton, Meghan M.; Aspen, Vandana; Wilfley, Denise E.; Taylor, C. Barr
Abstract: Objective: To investigate the association between binge features and clinical validators. Method: The Eating Disorder Examination assessed binge features in a sample of 549 college‐age women: loss of control (LOC) presence, binge frequency, binge size, indicators of impaired control, and LOC severity. Clinical validators were self‐reported clinical impairment and current psychiatric comorbidity, as determined via a semistructured interview. Results: Compared with women without LOC, those with LOC had significantly greater odds of reporting clinical impairment and comorbidity ( p s < 0.001). Among women with LOC ( n = 252), the indicators of impaired control and LOC severity, but not binge size or frequency, were associated with greater odds of reporting clinical impairment and/or comorbidity ( p s < 0.05). Dicussion: Findings confirm that the presence of LOC may be the hallmark feature of binge eating. Further, dimensional ratings about the LOC experience—and possibly the indicators of impaired control—may improve reliable identification of clinically significant binge eating. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)